THE LEXICON OF MAJAPAHIT CULINARY AT TROWULAN IN THE GLOBALIZATION ERA - Hendra, Hendra; Wahyuningputri, Rode Ayu; Putra, Aditya Nova; Levyta, Farah (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2021)
This research aims to describe the form of lingual, naming, and the meaning of lexicon and examines Majapahit Culinary by using a linguistic approach that has similar sounds with global tourism language. The problem studied in the process of naming the Majapahit Culinary that has the same sound as English as the international language. The ethnographic method is used to investigate the language and culture related to culinary based on the understanding of the local community. This research was conducted in Trowulan. Data collection uses in-depth interview methods and observations of the participation of informants. All data is reviewed using analisis domain, taxonomy, componential and themes, obtained from written sources including inscriptions and literature from Majapahit and from the time before and afterwards. The sources of research data are verbal words of the informants as speakers. Data collection was carried with participant observation techniques and interviews. Data analysis was carried out with four activities as collection, reduction, presentation and verification. The result of the Majapahit culinary analysis that has naming which can be used as the basis for the reference of the global sound are five Majapahit culinary, they are Letlet, Wok, Kwelon Dodol and Lepet. Those five Majapahit culinary will become a reference in the promotion of Majapahit culinary in international tourism.